Corpus Papyrorum Judaicarum Volume 4 - Hacham, Noah; Ilan, Ṭal 1956- (Berlin Boston De Gruyter Oldenbourg, 2020)
Frontmatter -- Acknowledgement -- Table of contents -- List of Abbreviations -- Explanatory Note -- Introduction -- Papyri of the Ptolemaic Period: Introduction -- Documentary papyri -- Literary Papyri -- Appendix 1: Additional Jewish papyri and ostraca -- Appendix 2: Ptolemaic inscriptions -- Appendix 3: Documents not considered Jewish and not included in N.CPJ IV -- Indices -- Table of Measurements -- Tables of sources, dates and locations of papyri in N.CPJ
The edition collects and presents all papyri and ostraca from the Ptolemaic period, connected to Jews and Judaism, published since 1957. It is a follow-up to the Corpus Papyrorum Judaicarum (= CPJ) of the 1950s and 60s, edited by Victor Tcherikover, which had consisted of three volumes – I devoted to the Ptolemaic period; II to the Early Roman period (until 117 CE); and III to the Late Roman and Byzantine periods. The present book, CPJ vol. IV, is the first in a new trilogy, and is devoted to the Ptolemaic period. The present and upcoming volumes supplement the original CPJ. They present over 300 papyri that have been published since 1957. They also include papyri in languages other than Greek (Hebrew, Aramaic, Demotic), and literary papyri which had not been included in the old CPJ. Aside from quite a number of papyri in these categories, the present volume (of over 100 documents) includes 21 papyri from Herakleopolis in Middle-Egypt that record the existence of a Jewish self-ruling body – the politeuma. These papyri put an end to a long-standing dispute over whether such a Jewish institution had ever existed in Egypt
Mode of access: Internet via World Wide Web.
In English
Keywords: Jews -- Egypt -- History -- Sources; HISTORY / Ancient / General; Biblische Papyri; Ptolemäisches Ägypten; Papyrologie; History / Jewish; Papyrology; Jews; Ptolemaic Egypt; Biblical Papyri; Diaspora